Derivative Problem Solving: Analysis of Problem Solving Errors in Solving Derivative Material - Wulandari, Sri; Caswita, Caswita; Wijaya, Agung Putra (Urogram Studi Pendidikan Matematika, Universitas Ivet, 2025)
Problem solving is a process that requires logical thinking to find solutions to the problems faced. Through this process, students will learn to develop appropriate strategies to solve the problems. This study aims to identify errors made by students in solving problems on the material of function derivatives. The method used in this study is descriptive qualitative, with data collection techniques carried out through previous literature reviews. The results of the study showed that students made mistakes at several stages, namely in understanding the problem, designing a solution strategy, implementing the solution, and at the re-checking stage. Based on the type of error, students made mistakes in terms of facts, concepts, principles, and operations. The proposed solution is to accustom students to be more careful in solving problems based on problem-solving steps, especially at the final checking stage, and to improve their mastery of algebraic operations and basic factoring techniques. Keywords: Problem Solving_Analysis of Errors_Derivative of Functions